A rare concurrence of monoclonal gammopathies in an older adult with tubulointerstitial nephritis and uveitis syndrome - Jian-hui Zhang; Jie Liu; Qian Chen; Dan-dan Ruan; Li-sheng Liao; Kai-ping Lin; Xiao-ling Zheng; Jie-wei Luo; Li Zhang (BMC Geriatrics)
Abstract Background Tubulointerstitial nephritis and uveitis (TINU) syndrome is prevalent among adolescent females and less prevalent among the older people. Additionally, although both disorders are linked to immune modulation, clinical instances of simultaneous diagnosis of TINU syndrome and monoclonal gammopathies (MG) are exceedingly rare. In this case report, we present a rare concurrence of monoclonal gammopathies in an older adult with TINU syndrome. Case presentation A 74-year-old woman with chronic bilateral anterior uveitis and a non-oliguric acute kidney injury developed TINU syndrome. Unexpectedly, immunofixation electrophoresis testing confirmed MG in the patient. Her renal histology showed tubulointerstitial degeneration, confirming TINU syndrome with MG. The patient tended to have monoclonal gammopathy of undetermined significance because her renal vascular light chain Kappa immunofluorescence showed significant positivity but no glomerular or tubular damage from monoclonal immunoglobulin deposition. The patient’s renal impairment was principally attributed to TINU syndrome, and after glucocorticoid treatment, ocular symptoms stabilized, renal impairment improved, and urine protein remained consistently negative. Conclusions The high incidence of disease in the old population results in increased disease complexity. This report emphasizes that TINU syndrome might be complicated by various additional conditions, including the unusual occurrence of coupled MG. A renal tissue biopsy is crucial for a differential diagnosis in cases of severe kidney injury. Patients with TINU and MG present distinct clinical manifestations and renal damage pathologies. The diagnosis of these patients requires consideration of clinical data and renal pathological alterations to guide treatment planning.